Pengkajian tentang kemampuan siswa dalam memahami konsep matematika serta pengaruhnya terhadap penerapan model pendekatan pembelajaran Makerspace STEAM dan kegiatan belajar siswa - Sari Suswati; Atikah Rakhmawati; Dinda Nasya Atin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines students' ability to understand mathematical concepts and the impact of implementing the Makerspace STEAM learning approach model on their learning activities. Makerspace STEAM integrates science, technology, engineering, art, and mathematics concepts in a practical, project-based learning context. This study uses a quantitative approach to evaluate students' increased understanding of mathematical concepts after engaging in Makerspace STEAM learning activities. It is hoped that the results of this research will provide better insight into the effectiveness of this learning model in improving student academic achievement in mathematics subjects.